Heat dissipation member and electronic device
By controlling the surface smoothness and interface roughness between the copper-diamond complex and metal film, the thermal conductivity of heat dissipation members is improved, achieving high thermal conductivity values.
Patent Information
- Application Number
- JP2023540289
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-08-06
- Filing Date
- 2022-07-27
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-07-27
AI Technical Summary
Existing heat dissipation members using copper-diamond complexes have limitations in heat conductivity, which can be improved by controlling the surface smoothness of the copper-diamond complex and the interface with a metal film.
The thermal conductivity of the heat dissipation member is enhanced by controlling the 10-point average height (RZ) and maximum height (RMAX) at the joining interface between the copper-diamond complex and the metal film, achieved through grinding and polishing to achieve a specific numerical range.
This approach results in a heat dissipation member with improved thermal conductivity, achieving values of 600W/m·K or higher, enhancing the heat dissipation characteristics.
Smart Images

Figure 0007623501000002 
Figure 0007623501000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a heat dissipation member and an electronic device. [Background technology]
[0002] Various developments have been made so far regarding heat dissipation components using copper-diamond composites. For example, the technology described in Patent Document 1 is known as this type of technology. Patent Document 1 describes, regarding a composite material of metal matrix and thermal conductor particles, that such a composite material contains ceramic particles such as diamond particles and SiC particles, and therefore it is difficult to polish and process the surface of the composite material to be flat (paragraph 0012). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 035796 Summary of the Invention [Problem to be solved by the invention]
[0004] However, as a result of investigations by the present inventors, it was found that there is room for improvement in the thermal conductivity of the heat dissipation member described in Patent Document 1 above. [Means for solving the problem]
[0005] After further investigation, the inventors discovered that the smoothness of the surface of a copper-diamond composite can be stably evaluated by using the ten-point average height Rz as an indicator, and further discovered that by controlling the numerical range of Rz at the bonding interface between a copper-diamond composite and a metal film to a predetermined value or less, the thermal conductivity of a heat dissipation component comprising such a composite and a metal film can be improved, thereby completing the present invention.
[0006] According to one aspect of the present invention, there is provided the following heat dissipation member and electronic device.
[0007] 1. A copper-diamond composite having a plurality of diamond particles dispersed in a copper-containing metal matrix; a metal film bonded to at least one surface of the copper-diamond composite; A heat dissipation member comprising: At the bonding interface between the copper-diamond composite and the metal film, the ten-point average height Rz calculated in accordance with JIS B 0601:2013 is 5 μm or more and 100 μm or less. Heat dissipation material. 2. The heat dissipation member according to 1., A heat dissipation member, wherein the copper-diamond composite has a bonding interface with the metal film with a maximum height Rmax of 180 μm or less, as calculated in accordance with JIS B 0601:2013. 3. The heat dissipation member according to 1. or 2., A heat dissipation component, wherein the copper-diamond composite has a thermal conductivity of 600 W / m·K or more. 4. A heat dissipation member according to any one of 1. to 3., When the particle size distribution of the diamond particles is measured using an image-type particle size distribution measuring device, the sphericity S at which the cumulative value becomes 50% in the volume particle size distribution of the sphericity of the diamond particles is 50 A heat dissipation member, wherein 5. A heat dissipation member according to any one of 1. to 4., When the particle size distribution of the diamond particles is measured using an image particle size distribution measuring device, the particle size D at which the cumulative value in the volumetric particle size distribution of the diamond particles is 50% is determined. 50 A heat dissipation member having a thickness of 300 μm or less. 6. A heat dissipation member according to any one of 1. to 5., and an electronic component provided on the heat dissipation member. Effect of the Invention
[0008] According to the present invention, there are provided a heat dissipation member having excellent thermal conductivity, and an electronic device using the same. [Brief description of the drawings]
[0009] [Figure 1] 2 is a schematic cross-sectional view showing an example of a configuration of a heat dissipation member according to the present embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In all drawings, similar components are given similar reference numerals and their explanations will be omitted as appropriate. Also, the drawings are schematic diagrams and do not correspond to the actual dimensional ratios.
[0011] The outline of the heat dissipation member of this embodiment will be described with reference to FIG. FIG. 1 is a schematic cross-sectional view showing an example of the configuration of a heat dissipation member according to this embodiment.
[0012] The heat dissipation member 100 of this embodiment includes a copper-diamond composite 30 in which a plurality of diamond particles 20 are dispersed in a copper-containing metal matrix 10, and a metal film 50 bonded to at least one surface of the copper-diamond composite 30.
[0013] The heat dissipation member 100 is configured so that the ten-point average height Rz calculated in accordance with JIS B 0601:2013 at the bonding interface 12 between the copper-diamond composite 30 and the metal film 50 is 5 μm or more and 100 μm or less.
[0014] According to the findings of the present inventors, the smoothness of the surface of a copper-diamond composite (hereinafter sometimes simply referred to as "composite") was repeatedly evaluated using the ten-point average height Rz as an index while adjusting the smoothness by grinding means under mild conditions. As a result, it was found that the thermal conductivity of the heat dissipation component can be improved by setting the numerical range of the index Rz at the bonding interface between the copper-diamond composite and the metal film to be equal to or less than the above upper limit.
[0015] Although the detailed mechanism is unclear, it is believed that by using a grinding method under gentle conditions to suppress the cracking and falling off of diamond particles while moderately smoothing the surface of the copper-diamond composite, the thickness of the metal film formed on the surface of the composite can be reduced, and as a result, the thermal conductivity of the entire heat dissipation member composed of the copper-diamond composite and the metal film can be improved. In other words, if the surface of the copper-diamond composite is not smoothed, it is necessary to form a thick metal film to fill in the large unevenness present on the surface, but if the metal film on the surface of the composite is made thick, the overall thermal conductivity may decrease.
[0016] The upper limit of the ten-point average height Rz at the bonded interface 12 of the copper-diamond composite 30 is 100 μm or less, preferably 80 μm or less, more preferably 60 μm or less, and more preferably 50 μm or less, thereby improving the thermal conductivity of the heat dissipation member. On the other hand, the lower limit of the ten-point average height Rz at the bonded interface 12 of the copper-diamond composite 30 is, for example, 5 μm or more, preferably 6 μm or more, and more preferably 7 μm or more, thereby making it possible to improve the adhesion between the composite and the metal film.
[0017] At the bonding interface 12 between the copper-diamond composite 30 and the metal film 50, the upper limit of the maximum height Rmax calculated in accordance with JIS B 0601:2013 is preferably 180 μm or less, more preferably 120 μm or less, and further preferably 80 μm or less. This can improve the thermal conductivity of the heat dissipation member. The lower limit of the maximum height Rmax at the bonding interface 12 with the metal film 50 is not particularly limited, but may be, for example, 1 μm or more.
[0018] The Rz and Rmax values at the bonding interface 12 between the copper-diamond composite 30 and the metal film 50 are substantially the same as the Rz and Rmax values on the surface of the copper-diamond composite 30 in the region where the metal film is to be formed before the metal film 50 is formed. The Rz and Rmax of the bonding interface 12 with the metal film 50 in the copper-diamond composite 30 may be measured by observing a vertical cross section of the heat dissipation member 100 with a digital microscope, extracting a contour curve of the bonding interface 12 from the cross-sectional observation image, and measuring the Rz and Rmax of the contour curve.
[0019] In this embodiment, it is possible to control the above Rz and Rmax by, for example, appropriately selecting the type and amount of each component contained in the copper-diamond composite, the manufacturing method of the copper-diamond composite, etc. Among these, for example, appropriately controlling the particle size and sphericity of the diamond particles, the grain size (grit) of the grinding stone used for grinding and polishing, and smoothing the surface of the copper-diamond composite under gentle conditions are listed as elements for setting the above Rz and Rmax within the desired numerical range.
[0020] The lower limit of the thermal conductivity of the heat dissipation member 100 is preferably 600 W / m·K or more, more preferably 630 W / m·K or more, and even more preferably 650 W / m·K or more, thereby improving the heat dissipation characteristics of the heat dissipation member. On the other hand, the upper limit of the thermal conductivity of the heat dissipation member 100 is not particularly limited, but is preferably 950 W / m·K or less, more preferably 900 W / m·K or less, and further preferably 870 W / m·K or less.
[0021] The configuration of the heat dissipation member of this embodiment will be described in detail.
[0022] The heat dissipation member 100 comprises a copper-diamond composite 30 and a metal film 50 .
[0023] (Copper-diamond composite) The copper-diamond composite 30 includes a copper-containing metal matrix 10 and a plurality of diamond particles 20 present in the metal matrix 10 .
[0024] The lower limit of the thermal conductivity of the copper-diamond composite 30 is preferably 600 W / m·K or more, more preferably 630 W / m·K or more, and even more preferably 650 W / m·K or more, thereby improving the heat dissipation characteristics of the heat dissipation member. On the other hand, the upper limit of the thermal conductivity of the copper-diamond composite 30 is not particularly limited, but is preferably 950 W / m·K or less, more preferably 900 W / m·K or less, and even more preferably 870 W / m·K or less.
[0025] The shape and size of the copper-diamond composite 30 can be appropriately set depending on the application. The copper-diamond composite 30 may have, for example, a plate shape, a block shape, a rod shape, or the like.
[0026] The metal matrix 10 may contain copper, or may contain a highly thermally conductive metal other than copper, that is, the metal matrix 10 is composed of a copper phase and / or a copper alloy phase.
[0027] The main component in the metal matrix 10 is preferably copper from the viewpoints of thermal conductivity and cost. The lower limit of the content of the main component copper is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, particularly preferably 80% by mass or more, and most preferably 90% by mass or more, based on 100% by mass of the metal matrix 10. This allows the good thermal conductivity of copper and copper alloys to be utilized. In addition, the same copper as the matrix can be used as the surface layer to ensure brazing properties and surface smoothness, and the formation of another surface coating layer can be omitted. The upper limit of the content of copper as the main component is not particularly limited, but may be 100% by mass or less, or may be 99% by mass or less, based on 100% by mass of the metal matrix 10 .
[0028] Examples of other highly thermally conductive metals include silver, gold, and aluminum. These may be used alone or in combination of two or more. When copper is combined with other highly thermally conductive metals, an alloy or composite material formed of copper and other highly thermally conductive metals may be used. The metal matrix 10 may be made of metals other than the highly thermally conductive metals as long as the effects of the present invention are not impaired.
[0029] When a copper alloy is used as the metal matrix 10, examples of the copper alloy include CuAg, CuAl, CuSn, CuZr, and CrCu.
[0030] The metal matrix 10 is, for example, a sintered body of metal powder containing copper (and other photothermal conductive metals as necessary). In this embodiment, the metal matrix 10 is composed of a sintered body in which at least a portion of the multiple diamond particles 20 are embedded.
[0031] The diamond particles 20 may be configured so that the entirety of the particles are embedded in the metal matrix 10, but at least a portion of one particle or particles is exposed at the bond interface 12 of the copper-diamond composite 30.
[0032] The diamond particles 20 include at least one of non-coated diamond particles having no metal-containing coating layer on the surface and coated diamond particles having a metal-containing coating layer on the surface. From the viewpoint of improving the adhesion between the diamond and the metal particles and dispersibility, the coated diamond particles are more preferable.
[0033] The lower limit of the volume ratio of diamond particles 20 in the copper-diamond composite 30 is preferably 10 volume % or more, more preferably 20 volume % or more, and further preferably 30 volume % or more. This can increase the thermal conductivity of the copper-diamond composite 30. On the other hand, the upper limit of the volume ratio of diamond particles 20 in the copper-diamond composite 30 is, for example, preferably 80 volume % or less, more preferably 70 volume % or less, and further preferably 60 volume % or less. This makes it possible to suppress large pores from remaining around the diamond particles 20 in the copper-diamond composite 30 due to a decrease in the adhesion of copper powder around the diamond particles 20, and to realize a structure with excellent manufacturing stability.
[0034] When using coated diamond particles as diamond particles 20, the metal-containing coating layer in the coated diamond particles may contain molybdenum, tungsten, chromium, zirconium, hafnium, vanadium, niobium, tantalum, and alloys thereof. These may be used alone or in combination of two or more. The metal-containing coating layer is configured to cover at least a part or the entire surface of the particle.
[0035] The sphericity and particle size of the diamond particles 20 are measured according to the following procedure. The particle size distribution of the diamond particles 20 is measured using an image-type particle size distribution measuring device (for example, Morphologi4 manufactured by Malvern). The particle size distribution includes a shape distribution and a particle diameter distribution. From the particle size distribution thus obtained, a volumetric particle size distribution of sphericity and a volumetric particle size distribution of particle diameter are calculated. Then, in the volumetric particle size distribution of the sphericity of the diamond particles 20, a sphericity of a predetermined cumulative value and a particle diameter of a predetermined cumulative value are obtained. Here, the sphericity and particle size are defined as follows. Sphericity: The ratio of the circumference of a circle that has the same area as the projected object to the circumference of the object. Particle diameter: The maximum length between two points on the contour of a particle image
[0036] The sphericity S of diamond particles 20 at which the cumulative value is 50% is measured according to the above procedure. 50 The lower limit is, for example, 0.70 or more, preferably 0.75 or more, more preferably 0.80 or more, and further preferably 0.9 or more. This increases the packing degree of the diamond particles 20 and increases the thermal conductivity of the composite. On the other hand, the above sphericity S 50 The upper limit of is not particularly limited, but may be, for example, 1.0 or less, or 0.99 or less.
[0037] The particle diameter D at which the cumulative value of diamond particles 20 is 50%, measured according to the above procedure, 50The upper limit is, for example, 300 μm or less, preferably 270 μm or less, more preferably 250 μm or less, further preferably 220 μm or less, particularly preferably 200 μm or less, and most preferably 180 μm or less. This increases the degree of filling of the diamond particles 20 and increases the thermal conductivity of the composite. The above particle size D 50 The lower limit is not particularly limited, but may be, for example, 5 μm or more.
[0038] In the heat dissipation member 100, the multiple diamond particles 20 may be configured to include a first diamond particle having at least a portion of its surface exposed from the metal matrix 10, and a second diamond particle having its entire surface embedded in the metal matrix 10. The heat dissipation member 100 may also have a connection structure in which one of the first diamond particles is in contact with one of the second diamond particles. In the connection structure, at least one, two or more, or four or more of the second diamond particles may be in continuous contact with each other. This can improve the thermal conductivity of the heat dissipation member 100. The above-mentioned connection structure is confirmed in at least one cross section of the heat dissipation member 100 in the thickness direction.
[0039] The upper limit of the flatness of the copper-diamond composite 30 calculated in accordance with JIS B 0621: 1984 is, for example, 40 μm or less, preferably 39 μm or less, and more preferably 38 μm or less, which can improve the adhesion between the composite and the metal film. On the other hand, the lower limit of the flatness is not particularly limited, but may be 1 μm or more.
[0040] The upper limit of the ten-point average height of the diamond particle surface exposed at the surface (bonding interface 12) of the copper-diamond composite 30, calculated in accordance with JIS B 0601: 2013, is, for example, 5 μm or less, preferably 4 μm or less, and more preferably 3 μm or less. This can improve the adhesion between the composite and the metal film. On the other hand, the lower limit of the ten-point average height of the diamond particle surface is not particularly limited, but may be 0.1 μm or more.
[0041] (Metal Film) The metal film 50 needs to be formed on at least one surface of the copper-diamond composite 30, and may be formed on both surfaces of the copper-diamond composite 30 in the form of a flat plate, for example.
[0042] The metal film 50 may contain one or more metals selected from the group consisting of copper, silver, gold, aluminum, nickel, zinc, tin, and magnesium. It is preferable that the metal film 50 contains the same metal as the main component metal in the metal matrix 10, and it is preferable that the metal film 50 contains at least copper or a copper alloy.
[0043] The content of the main component copper is preferably 50 mass% or more, more preferably 60 mass% or more, even more preferably 70 mass% or more, particularly preferably 80 mass% or more, and most preferably 90 mass% or more, based on 100 mass% of the metal film 50. The upper limit of the content of copper as the main component is not particularly limited in 100 mass % of the metal film 50, but may be 100 mass % or less, or may be 99 mass % or less.
[0044] The upper limit of the film thickness of the metal film 50 is preferably 150 μm or less, more preferably 120 μm or less, and further preferably 100 μm or less, so that the thermal conductivity of the heat dissipation member can be increased. On the other hand, the lower limit of the film thickness of the metal film 50 is preferably 10 μm or more, more preferably 15 μm or more, and further preferably 20 μm or more, so that the adhesive strength with the composite and the durability of the metal film 50 itself can be increased.
[0045] The metal film 50 is obtained by, for example, a sputtering method or a plating method. The average crystal grain size of the metal in the metal film 50 is preferably 5 nm or more and 50 nm or less, more preferably 10 nm or more and 40 nm or less, and further preferably 20 nm or more and 30 nm or less. The average crystal grain size is measured by a transmission electron microscope (TEM).
[0046] The electronic device of this embodiment includes the above-described heat dissipation member and an electronic component provided on the heat dissipation member.
[0047] Examples of electronic components include semiconductor elements, etc. Specific examples of semiconductor elements include power semiconductors, image display elements, microprocessor units, and laser diodes.
[0048] Heat dissipation members are used in heat sinks, heat spreaders, etc. A heat sink dissipates heat generated during operation of a semiconductor element to the external space, and a heat spreader transfers heat generated by the semiconductor element to other members.
[0049] The electronic components may be mounted directly on the heat dissipation member or indirectly via a ceramic substrate or the like.
[0050] An example of a method for manufacturing the heat dissipation member of this embodiment will be described.
[0051] An example of a method for manufacturing a heat dissipation member includes a raw material mixing step, a sintering step, a smoothing step, and a film forming step.
[0052] In the raw material mixing step, a copper-containing metal powder, such as copper powder, and diamond particles are mixed to obtain a mixture. The raw material powders can be mixed by various methods, such as dry and wet methods, but a dry mixing method may also be used.
[0053] In the firing step, the mixture of metal powder and diamond particles is fired to obtain a composite sintered body of copper and diamond particles. The firing temperature can be appropriately selected according to the metal species contained in the metal powder, but in the case of copper powder, it is preferably 800°C or more and 1100°C or less, more preferably 850°C or more and 1000°C or less. By setting the firing temperature at 800°C or more, the copper-diamond composite is densified and a desired thermal conductivity is obtained. By setting the firing temperature at 1100°C or less, deterioration due to graphitization of the interface of diamond particles is suppressed, and the decrease in the inherent thermal conductivity of diamond can be prevented. The firing time is not particularly limited, but is preferably 5 minutes or more and 3 hours or less, more preferably 10 minutes or more and 2 hours or less. By setting the firing time to 5 minutes or more, the copper-diamond composite is densified and the desired thermal conductivity is obtained. By setting the firing time to 3 hours or less, the formation of carbides and thickening of the film occurs between the diamond in the coated diamond particle and the metal covering the surface, which can suppress the decrease in thermal conductivity due to phonon scattering and the cracks caused by the difference in linear expansion coefficient. In addition, the productivity of the composite can be improved.
[0054] In the firing step, either pressureless sintering or pressure sintering may be used, but pressure sintering is preferred in order to obtain a dense composite body.
[0055] Examples of pressure sintering methods include hot press sintering, spark plasma sintering (SPS), hot isostatic pressure sintering (HIP), etc. In the case of hot press sintering or SPS sintering, the pressure is preferably 10 MPa or more, more preferably 30 MPa or more. On the other hand, in the case of hot press sintering or SPS sintering, the pressure is preferably 100 MPa or less. By setting the pressure to 10 MPa or more, the copper-diamond composite is densified and a desired thermal conductivity is obtained. By setting the pressure to 100 MPa or less, diamond cracks are generated, and the diamond interface is increased and the adhesion between the diamond fracture surface and the metal is reduced, which prevents the inherent thermal conductivity of diamond from being reduced.
[0056] In the smoothing step, at least a part of the surface of the composite sintered body is ground and polished to obtain a copper-diamond composite.
[0057] In the film-forming step, a metal film is formed on at least a portion of the smoothed surface of the copper-diamond composite.
[0058] The metal film may be formed by a common method such as sputtering, plating, or pressure co-firing using copper foil, but sputtering may also be used to make the film thinner. In addition, at least a part of the surface of the metal film may be subjected to surface grinding and polishing, which can improve the surface smoothness of the metal film after the film formation process.
[0059] In addition, an annealing step may be added between the firing step and the smoothing step. Furthermore, prior to the film formation step, the copper-diamond composite may be subjected to a process such as shaping or drilling.
[0060] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0061] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the descriptions of these examples.
[0062] <Production of composites and heat dissipation components> Example 1 The copper powder and diamond particles (Mo coated) were weighed out to a ratio of 50 volume %:50 volume %, and the weighed powders were mixed uniformly in a V-type mixer to obtain a mixture (raw material mixing step). Next, the resulting mixture was filled into a mold using an SPS sintering device and heated and sintered at 900°C for 1 hour under a pressure of 30 MPa, obtaining a disk-shaped composite sintered body consisting of multiple diamond particles dispersed in a copper matrix (sintering process).
[0063] The particle size distribution (shape distribution / particle size distribution) of the raw diamond particles was measured using an image-based particle size distribution measuring device (Malvern, Morphologi4). The sphericity S at which the cumulative value reaches 50% in the volumetric particle size distribution of diamond particles 50 In the volumetric particle size distribution of diamond particles, the particle diameter D at which the cumulative value is 50% 50 These values were calculated as the average of two measurements. The sphericity and particle size were defined as follows: Sphericity: The ratio of the circumference of a circle that has the same area as the projected object to the circumference of the object. Particle diameter: The maximum length between two points on the contour of a particle image As a result, the sphericity S of the diamond particles used 50 is 0.9, particle size D 50 was 200 μm.
[0064] Both sides of the obtained composite sintered body were smoothed by surface grinding and polishing using a #400 grindstone to obtain a copper-diamond composite (ground composite sintered body) with an outer diameter of 30 mm and a thickness of 3 mm (smoothing step).
[0065] The content of diamond particles in the copper-diamond composite was 50.8% by volume. The surface roughness and flatness of one of the smoothed surfaces of the copper-diamond composite (surface area spanning from the copper matrix to the diamond particles) were observed and measured using a digital microscope (VHX-8000, Keyence). As a result, the ten-point average height Rz calculated in accordance with JIS B 0601:2013 was 20.5 μm, the maximum height Rmax was 24.3 μm, and the flatness calculated in accordance with JIS B 0621:1984 was 30.1 μm. Furthermore, the ten-point average height of the diamond particle surface exposed on the surface of the copper-diamond composite (ten-point average height Rz of the diamond surface) was 1.5 μm. The thermal conductivity of the copper-diamond composite was measured by the laser flash method, and was found to be 753 W / m K. The laser flash method was performed at room temperature with the sample surface coated with carbon.
[0066] Thereafter, a Cu film having a thickness of 30 μm was formed on each of both sides of the copper-diamond composite by sputtering, to obtain a heat dissipation member composed of Cu film / copper-diamond composite / Cu film (film forming step). The thermal conductivity of the heat dissipation material was measured by the laser flash method and found to be 748 W / m·K. The average crystal grain size of the Cu film in the heat dissipation member was 26 nm. The crystal grain size was measured by dividing the grain size by 1 μm from the structure obtained by a transmission electron microscope. 2 It was calculated from the number of crystal grains in the sample.
[0067] (Examples 2 to 8, Comparative Example 1) A composite and a heat dissipating member were obtained in the same manner as in Example 1, except that the particle size and sphericity of the diamond particles in Table 1 were changed and the grinding and polishing conditions were changed to those described in the remarks. The obtained composite and heat dissipation member were evaluated in the same manner as in Example 1.
[0068] [Table 1]
[0069] As shown in Table 1, it was found that the heat dissipation members of Examples 1 to 8 were able to achieve superior thermal conductivity compared to Comparative Example 1.
[0070] This application claims priority based on Japanese Patent Application No. 2021-129856, filed on August 6, 2021, the disclosure of which is incorporated herein in its entirety. [Explanation of symbols]
[0071] 10 Metal Matrix 12 Bonding interface 20 Diamond particles 30 Copper-diamond composite 50 Metal Film 100 Heat dissipation member
Claims
1. a copper-diamond composite having a plurality of diamond particles dispersed in a copper-containing metal matrix; a metal film bonded to at least one surface of the copper-diamond composite; A heat dissipation member comprising: the copper-diamond composite has a ten-point average height Rz of 5 μm or more and 100 μm or less at a bonding interface with the metal film, the ten-point average height Rz being calculated in accordance with JIS B 0601:2013; Heat dissipation material.
2. The heat dissipation member according to claim 1 , A heat dissipation member, wherein the copper-diamond composite has a maximum height Rmax of 180 μm or less at a bonding interface with the metal film, the maximum height Rmax being calculated in accordance with JIS B 0601:2013.
3. The heat dissipation member according to claim 1 or 2, The copper-diamond composite has a thermal conductivity of 600 W / m·K or more.
4. The heat dissipation member according to claim 1 or 2, When the particle size distribution of the diamond particles is measured using an image-type particle size distribution measuring device, the sphericity S at which the cumulative value becomes 50% in the volume particle size distribution of the sphericity of the diamond particles is 50 A heat dissipation member, wherein the ratio of the heat dissipation coefficient to the heat dissipation coefficient is 0.70 or more.
5. The heat dissipation member according to claim 1 or 2, When the particle size distribution of the diamond particles is measured using an image particle size distribution measuring device, the particle size D at which the cumulative value in the volumetric particle size distribution of the diamond particles is 50% is determined. 50 A heat dissipation member having a thickness of 300 μm or less.
6. The heat dissipation member according to claim 1 or 2; and an electronic component provided on the heat dissipation member.
Citation Information
Patent Citations
Copper-diamond composite material and production method thereof
JP2015160996A
Semiconductor element mounting substrate, semiconductor device using the same, and process for producing semiconductor element mounting substrate
WO2007074720A1
Heat dissipation member and method for producing heat dissipation member
WO2016035796A1